Las dos orillas. Desde esta orilla - Pallares, Berta (Revista de Filología Románica, 2008)
This article, conceived as a tribute to Alonso Zamora Vicente, proposes a detailed work on the Danish version of the Danza de la Muerte, related to the Scandinavian literatures in the Middle Ages.